Caracterização dos parâmetros de qualidade da água do Igarapé Grande, Boa Vista, Roraima - Pereira Junior, Ubiracy (2015)
The research aimed to characterize the water from the Igarapé Grande, located in Boa Vista City, Roraima, using microbiological and physical-chemical indicators. The Igarapé watershed is located in Boa Vista City, state of Roraima, at Rio Branco right bank. Igarapé Grande is an urbanized water body, from its source to its mouth. For this study, we selected five points for water samples collection from the Igarapé Grande. Point 1 is located in Araceli bridge, Joquei Club district, and is approximately 1.6 km away from the point 3 (ETE-Boa Vista old chute). Point 2 is located near the Centenário Bridge, Brigadeiro district, and its distance from the chute (P3), is approximately 92 m. While Point 4 located in chute downstream, near to the Centenário Bridge, Brigadeiro district, about 40 m from the chute. Point 5, is near to the BR-174 bridge, 13 de Setembro district and its distance from the chute is about 1,15 km. The samples were divided into subsamples for microbiological analyzes (total coliforms, fecal coliforms and heterotrophic bacteria), physical-chemical (temperature, dissolved oxygen, hydrogenionic potential, electrical conductivity, biochemical oxygen demand, ammonia, nitrate, nitrite, chloride, phosphate and turbidity) and detection of cyanotoxins (microscystin and cylindrospermopsin). The collection for algae identification was performed with a plankton net help with mesh opening of 60 μm. Afterwards the subsamples were placed in glass bottles (amber) with 500 mL capacity and immediately fixed with lugol acetic solution 5%. The monitoring of limnological parameters of the Igarapé Grande, was performed bimonthly way, between the period of August 2014 to June 2015. The density changeability of the total coliforms, thermotolerant and heterotrophic bacteria in the Igarapé Grande point to the concentrate pollution. The phytoplankton algae were identified and distributed in five phylums, six classes, 10 orders, 14 families and 20 genus of algae. Among the found phylums there are Chlorophyta, Euglenophyta, Bacilariophyta, Heterokontophyta and Cyanophyta. In the samples tested were detected concentrations of microcystin and cylindrospermopsin by hight performance liquid chromatography (HPLC) with detection by photo diode linear array. While relations between the physicochemical parameters of the water body in the dry and rainy seasons point to a trendency that was maintained in the six collections at each point noting that the individual fluctuations at each point did not influence the behavioral consistency.